Thermoelectric performance enhancement of lead-free germanium telluride-based materials - Tan, Xian Yi (Nanyang Technological University, 2023)
The recovery of waste heat through the use of thermoelectric (TE) devices is an attractive solution to alleviate the growing global energy demands and fossil fuel shortage, considering that about two-thirds of the energy input to ubiquitous processes that involve heat engines are constantly being lost as waste heat. As the conversion efficiency of devices using traditional state-of-the-art materials remain too low to be widely commercially competitive, there is a desperate need for materials with high figure-of-merit (ZT) values. Such high ZT materials usually have combined traits of good heat insulation, metal-like electrical conductivities, and high voltage response to a temperature difference. The later two properties determine its electrical response. GeTe is an emerging semiconductor TE material with its peak performance in the medium-temperature range (350 – 550 °C), where most optimized state-of-the-art GeTe-based materials can achieve ZTs of >2 at ~450 °C, where those with the best efficiencies, wide-temperature range average ZTs and near-room-temperature (50 °C) ZTs all contain lead (Pb) atoms replacing some Ge atoms in the GeTe crystal (i.e. Pb doping), which are unfortunately highly toxic and will hinder the wide-spread usage of GeTe-based TE devices in the future. Therefore, the objectives of this thesis largely involve achieving comparable performances without Pb, by modifying Pb-free GeTe materials through: (i) alloying with a heat insulating phase, (ii) dilute doping for maximum electrical response properties at 50 °C, and (iii) stacking onto another TE material. The findings of this thesis will pave the way to less toxic GeTe-based devices with greater practical versatility.